Modern JavaScript for beginners. - Dixon, Chris (Packt Publishing, 2022)
JavaScript is a core technology programming language of the World Wide Web with HTML and CSS. Almost all websites use JavaScript as a webpage client, often with third-party libraries. JavaScript is a multi-paradigm that supports event-driven, functional, and imperative coding with APIs to work with text, dates, regular expressions, data structures, and the Document Object Model (DOM). This course begins with a foundation in JavaScript, covering arrays, functions, objects, events, DOM, web APIs, loops, math, date and timers, and canvas drawing. Create a video player with customized controls and a fun shape-drop game. Explore trickier concepts such as async JavaScript, scope, hoisting, and closures, before finishing two projects. Finally, you will build a small app called "Leaving so Soon" to woo visitors with an offer when trying to leave the website and a fully functional JavaScript image carousel. By the end of the course, you will understand the concepts of JavaScript programming and advanced concepts like Async JavaScript, scope, hoisting, and closure. You can apply the concepts in project samples from a real-world scenario to understand JavaScript programming. You will be able to create apps and games using JavaScript programming. What You Will Learn Learn the basics of arrays, functions, objects, events, and the DOM Understand the concepts of using loops and conditional statements Know about objects, math, date, timers, and drawing on canvas Explore complex Async JavaScript, scope, hoisting, and closure Build a working video player with fully customized controls Create an app called "Leaving so soon" to woo visitors with an offer Audience This beginner-focused course targets AI developers, web content developers, and front-end interface developers working on other platforms wanting to learn JavaScript programming. The course is aimed at those new to JavaScript or having little knowledge about JavaScript and looking for an extensive course to advance to the intermediate/advanced levels. To optimize the course, you do not require any knowledge of JavaScript; however, prior knowledge of HTML and CSS is desirable. About The Author Chris Dixon: Chris Dixon is a self-employed web developer teaching others through training courses. Chris offers freelance web development and training workshops on various topics, including HTML, CSS, JavaScript, Vue.js, NUXT.js, WordPress (custom theme development), Mongo/Mongoose, PostgreSQL, Express, Firebase, and Supabase. Chris is also involved in building Shopify ecommerce solutions, including custom apps and theme development. Chris has vast experience in GraphQL, Keystone CMS, and many other front-end/full-stack skills. He is additionally a regular Shopify user in creating and managing online stores and editing/creating custom liquid templates.